Body Composition and Physical Performance by Playing Position in Amateur Female Soccer Players - Herrera-Valenzuela, T; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study analyzed differences in body composition, jump performance, running speed, and ball-kicking speed according to playing position in amateur female soccer players. This cross-sectional study involved 160 females distributed into groups of goalkeepers (n = 20), defenders (n = 38), midfielders (n = 52), and forwards (n = 50), with a mean age of 27.1 ± 3.23 years. They were assessed for body fat percentage (BFP), fat-free mass (FFM), squat jump, countermovement jump, drop jump (DJ), and running sprint speed for 10 m, 20 m, and 30 m, and ball-kicking speed (BKS) with both feet. Significant differences were found between groups in FFM (F(3,96) = 17.4; p = 0.000) and BFP (F(3,96) = 7.00; p = 0.000), with a higher FFM in midfielders with respect to goalkeepers (p = 0.00; ES = 1.77; ∆ = 27%), defenders (p = 0.00; ES = 2.14; ∆ = 26.5%), and forwards (p = 0.00; ES = 1.13; ∆ = 15.8%), and a lower BFP in midfielders with respect to goalkeepers (p = 0.00; ES = 1.41; ∆ = 26.7%) and forwards (p = 0.00; ES = 1.05; ∆ = 27%). In addition, significant differences were found between groups in DJ (F(3,96) = 20.8; p = 0.000), with midfielders achieving greater height compared to goalkeepers (p = 0.00; ES = 1.94; ∆ = 25.1%), defenders (p = 0.00; ES = 1.59; ∆ = 19%), and forwards (p = 0.00; ES = 1.73; ∆ = 16.3%). Significant differences were found between groups in BKS for dominant (F(3,96) = 5.84; p = 0.001) and non-dominant (F(3,96) = 3.29; p = 0.02) feet, and these were lower in goalkeepers than defenders (p = 0.00; ES = 0.99; ∆ = 8.83%) and midfielders (p = 0.00; ES = 1.21; ∆ = 11.8%). In conclusion, midfielders presented significantly better body composition and physical performance than other playing positions. © 2024 by the authors.